2007
DOI: 10.1007/s00436-007-0516-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigating a persistent coccidiosis problem on a commercial broiler–breeder farm utilising PCR-coupled capillary electrophoresis

Abstract: In the present study, we utilised a polymerase-chain-reaction-coupled capillary electrophoresis (CE) approach to investigate the epidemiology of Eimeria species on a broiler-breeder farm in Victoria, Australia. The Eimeria populations of two flocks vaccinated against coccidiosis were followed over an 11-week period. All seven recognised Eimeria species of chickens were detected in both flocks. One flock suffered increased morbidity and mortality in its eighth week and had consistently higher Eimeria oocyst cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 22 publications
5
31
0
Order By: Relevance
“…Research within our laboratory has shown that such a library of prototype PCR products (which include SYTO † 9) can be reused several times without a detectable effect on the melting curve temperature (results not shown). This is in agreement with previous studies (Herrmann et al, 2006;Morris et al, 2007b) in which SYBR Green I was compared with SYTO † 9, with SYTO † 9 shown to produce highly reproducible DNA melting profiles and to be less selective in its incorporation into particular amplicons.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Research within our laboratory has shown that such a library of prototype PCR products (which include SYTO † 9) can be reused several times without a detectable effect on the melting curve temperature (results not shown). This is in agreement with previous studies (Herrmann et al, 2006;Morris et al, 2007b) in which SYBR Green I was compared with SYTO † 9, with SYTO † 9 shown to produce highly reproducible DNA melting profiles and to be less selective in its incorporation into particular amplicons.…”
Section: Discussionsupporting
confidence: 92%
“…Rapid real-time PCR assays specific to four species of Eimeria have recently been described (Blake et al, 2008) but require separate reaction tubes for detection of each of the species tested. Also, other PCR-coupled techniques such as high-throughput capillary electrophoresis, high-resolution electrophoretic procedures and singlestrand restriction fragment length polymorphism analysis have found applicability (Woods et al, 2000a(Woods et al, , 2000bGasser et al, 2005;Morris et al, 2007aMorris et al, , 2007b. While these approaches have been useful and effective, they have relied on the high-resolution analysis of denatured PCR products on electrophoretic gels, taking a day to carry out.…”
mentioning
confidence: 97%
“…Coccidiosis is a parasitic disease resulting from an intracellular protozoan parasite of the genus Eimeria (Saif 2003), which causes damage to the intestinal tissue, decreases feed intake and absorption of nutrients and also increases the susceptibility to secondary bacterial infections (Morris et al 2007). Coccidiosis is of great economic impact for poultry industry and causes huge worldwide economic losses estimated up to US $3 billion annually (Dalloul and Lillehoj 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In poultry, there are seven recognized species that develop in certain parts of the gut (site-specific), each causing a separately recognizable disease [56]: E. acervulina, E. tenella, E. maxima, E. necatrix, E. mitis, E. praecox and E. brunetti. These species of Eimeria have different pathogenicity; E. tenella and E. necatrix are the most pathogenic and cause bloody lesions, high morbidity and mortality in naive chickens [19, 32]; E. acervulina , E. maxima and E. brunetti also cause clinical diseases; E. praecox and E. mitis , although considered to be relatively non-pathogenic [32], do cause a reduced feed conversion efficiency and growth rate [56]. Also, infection with certain species of Eimeria was demonstrated to be implicated in predisposing birds to necrotic enteritis [55], through lesions that compromise gut integrity, and allow the proliferation of pathogens [52].…”
Section: Introductionmentioning
confidence: 99%